A few drops of bitters - McKevett, G. A. (McKevett, G. A. Savannah Reid mystery., 2021)
When the jet-setting, brain surgeon husband of her veterinarian friend dies after making a champagne toast at a star-studded party, plus-sized private eye Savannah Reid investigates.